Kajian Identifikasi Risiko Pada Tahap Pelaksanaan Proyek Konstruksi: Studi Kasus Multiple Project Management - Saut Batara Siahaan; Manlian Ronald A Simanjuntak (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Risk identification is a part of the Risk Management Process. Multiple Project Management is fundamentally different from a single project. In multiple projects, there is the connectedness of resource allocation and the possibility of conflict between the projects. The research problems analysed are: What is the meaning of risk in a construction project? What is the picture of the multiple projects? What are the potential risks in the multiple projects? What are the recommendations resulting? This research is limited for implementation of construction projects in industrial facilities in Indonesia. Several literature reviews are used as the basis for analysis such as PMBOK, Guide 6th Edition as well as various relevant research results. The research process carried out to examine various things about risks in multiple projects, the Risk Management process, review various relevant research and provide recommendations. The conclusions of this study are: risks are various potentials that can affect the implementation of construction projects, necessary to anticipate risks in the construction projects, potential risks can occur in the all-construction phase, and as results, it is observed that there are various aspects of prevention against risks to minimize the negative impacts in the multiple projects.